2017
DOI: 10.2139/ssrn.3035166
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and Opportunities for Integrated Modeling of Climate Engineering

Abstract: The Paris Agreement has set stringent temperature targets to limit global warming to 2°C above preindustrial level, with efforts to stay well below 2°C. At the same time, its bottom-up approach with voluntary national contributions makes the implementation of these ambitious targets particularly challenging. Climate engineering -both through carbon dioxide removal (CDR) and solar radiation management (SRM) -is currently discussed to potentially complement mitigation and adaptation. Results from integrated asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…23 Canadell and Raupach (2008), Strengers et al (2008), Edmonds et al (2013), Fuss et al (2013, Kriegler et al (2013a), Tavoni and Socolow (2013), Bibas and Méjean (2014), Blanford et al (2014a), Kriegler et al (2014), Popp et al (2014), Selosse and Ricci (2014), Vaughan and Gough (2016), Gambhir et al (2017), Marcucci et al (2017, Mintenig et al (2017), Tavoni et al (2017, Holz et al (2018), Obersteiner et al (2018, Sanchez et al (2018), Séférian et al (2018), Strefler et al (2018, Vaughan et al (2018) Others O7…”
Section: Mitigation Pathway Dynamics D7mentioning
confidence: 99%
See 3 more Smart Citations
“…23 Canadell and Raupach (2008), Strengers et al (2008), Edmonds et al (2013), Fuss et al (2013, Kriegler et al (2013a), Tavoni and Socolow (2013), Bibas and Méjean (2014), Blanford et al (2014a), Kriegler et al (2014), Popp et al (2014), Selosse and Ricci (2014), Vaughan and Gough (2016), Gambhir et al (2017), Marcucci et al (2017, Mintenig et al (2017), Tavoni et al (2017, Holz et al (2018), Obersteiner et al (2018, Sanchez et al (2018), Séférian et al (2018), Strefler et al (2018, Vaughan et al (2018) Others O7…”
Section: Mitigation Pathway Dynamics D7mentioning
confidence: 99%
“…2014),Humpenöder et al (2014),Kober et al (2014),Popp et al (2014),Selosse and Ricci (2014),,van Sluisveld et al (2013),Eom et al (2015),Leibowicz et al (2016),Mouratiadou et al (2016),Calvin et al (2017),Marcucci et al (2017),Tavoni et al (2017),Sanchez et al (2018),Séférian et al (2018), Vaughan et al reductions rates have been scarcely reported in the past but remain central to climate action. Mid-term gross CO2 emission reduction rates envisaged in scenarios have no historical precedence.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…BECCS has furthermore been much discussed as a policy option in the integrated assessment modelling (IAM) literature (e.g. Fuss et al 2014, Azar et al 2013, Smith et al 2016, Klein et al 2014, Tavoni et al 2017. Vaughan and Gough (2016) found, however, that assumptions concerning the availability of BECCS in future IAM scenarios are too optimistic according to expert judgment, and this could indeed lead to overshoot of temperature targets with a substantial bearing on near-term mitigation options.…”
Section: Introductionmentioning
confidence: 99%